A primer on microeconomics. - Beveridge, Thomas M. (Economics and public policy collection., 2018)
Economics, far from being the "dismal science," offers us valuable lessons that can be applied to our everyday experiences. At its heart, economics is the science of choice and a study of economic principles that allows us to achieve a more informed understanding of how we make our choices, regardless of whether these choices occur in our everyday life, in our work environment, or at the national or international level. The present two-volume text represents a commonsense approach to basic microeconomic principles. It is directed toward all students, but particularly toward those within business school settings, including students beginning an advanced business degree course of study. It will deliver clear statements of essential economic principles, supported by easy-to-understand examples, and uncluttered by extraneous material, the goal being to provide a concise readable primer that covers the substance of microeconomic theory. Over the course of the two volumes, the text will look at the efficient operation of competitive markets and what may cause those markets to fail, the benefits derived from trade, profit maximization, the consequences of choice, and the implications of imperfect competition.